The dynamics of business investment following banking crises and normal recessions - Nils Jannsen (Kiel Institute for the World Economy (IfW), 2015)
I empirically analyze the dynamics of business investment following normal recessions (declines in business investment that are not associated with banking crises) and banking crises. Using a panel of 16 advanced economies, I find evidence for significant non-linear trend reversion or bounce-back effects on the level of business investment following normal recessions, i.e., the deeper the previous recession was, the higher the growth rate of business investment will be. The trend reversion effect is absent when a decline in business investment is associated with a banking crisis. As a consequence, normal recessions do not have significant permanent effects on the level of business investment, whereas banking crises have large and significant permanent effects. The results are in line with important theories and other empirical results on business cycle dynamics.
Keywords: E32; C33; 330; business investment; business cycle; recovery; banking crises; asymmetries